Bacterial cellulose-based indicators for freshness monitoring in intelligent packaging of fresh-cut jackfruit - Iswati, Nurul; Dirpan, Andi; Syarifuddin, Adiansyah; Hidayat, Serli Hatul; Ainani, Andi Fadiah; Majumder, Soumya (Hasanuddin University Food Science and Technology Study Program, 2025)
Fresh-cut fruits are highly perishable due to rapid physiological, chemical, and microbiological changes during storage, which limit their shelf life and consumer acceptance. To address this challenge, this study developed bacterial cellulose-based indicator labels combined with colorimetric solutions to provide real-time information on the quality of fresh-cut jackfruit as part of intelligent packaging. This study focused on identifying the most suitable color indicator for jackfruit and evaluating the performance of the bacterial cellulose-based label in detecting freshness. Indicators were tested during 24 hours of storage at room temperature, and their responses were correlated with key quality parameters, including O₂ and CO₂ concentrations, firmness, pH, total soluble solids, vitamin C, total acidity, and microbial counts. The results demonstrated that the developed indicator effectively responded to quality changes, with color shifts reflecting respiration activity, tissue softening, biochemical alterations, and microbial growth. Correlation analysis confirmed that the indicator’s color changes were consistent with the deterioration of fresh-cut jackfruit, particularly after 20 hours, when microbial counts exceeded acceptable limits. Overall, intelligent packaging based on bacterial cellulose indicators offers an accurate, consumer-safe, and sustainable solution for monitoring fruit freshness.